Análise da mudança organizacional de uma indústria fumageira rumo à excelência: estudo de caso - Pereira, Aline Soares (2006)
Expansion of the international market and constant changes in the external environment require organizations and their processes to become more and more flexible. New impositions of the market turn the concepts of a mechanicist system into an inter-relation system at organizations. Today s organizations need to break their paradigms and prepare their employees for this process of continuous changes because only so they will achieve good results and will help their clients in a fast and efficient way. The research aims to analyze the implementation of changes in the productive process of a tobacco industry based on the excellence of the business. This subject choice was based on the importance of comprehending how the employees involved in the organizational change process face the changes that influence the way of performing their routine activities, the quality of life, and the organizational environment. The productive process of company X has faced profound transformations aiming to become more competitive in its area. The research aims to identify aspects that were noticed in this change, and it was based on the perception of the employees of the company. The criteria and principles of the excellence model of Fundação Nacional da Qualidade FNQ were used to get the data regarding the perception of the employees of the company. The accordance of this research to the FNQ criteria is important because the organization that follows the concepts of the program is considered a reference of excellence. The Excellence Criteria constitute a systemic model of management used by many organizations worldwide. They are based on principles that are essential to achieve excellence in the performance of the business.